Moving to Mac OS X Painlsessly - Gene Steinberg (Mc Graw Hill, 2003)
Mac OS X is a major departure from the older versions of the Macintosh operating system. For one thing, it sits atop a UNIX base and, thus, has an extraordinary number of powerful features. In addition, the new user interface, code-named Aqua, bears close resemblance to the Mac user experience on the surface, but there's a lot of difference, which you'll see when you explore the lay of the land.